ARCHAEOLOGICAL EVIDENCE FROM GUA LADORI, NORTH KONAWE, SOUTHEAST SULAWESI - Sabri, M; Permana, R. Cecep Eka (UI Scholars Hub, 2024)
The presence of archaeological sites, specifically caves, in North Konawe Regency provides evidence of human habitation dating back to prehistoric times. Despite the challenges posed by difficult terrain and limited access, which hinder archaeological research, the Gua Ladori site in Bendewuta Village, Oheo District, North Konawe, is notable for its rich assemblage of artifacts. This study aims to identify the archaeological remains at Gua Ladori and assess their significance within the prehistoric context of Sulawesi, with a particular focus on North Konawe. The research methodology involves three stages: data collection, data processing and analysis, and conclusion drawing. The findings reveal a diverse array of artifacts, including bone fragments, ceramics (earthenware, stoneware, and porcelain), stone tools, shell remains, and rock art. Analysis indicates that the earthenware and porcelain ceramics are likely from the 14th to 17th centuries AD